Immunosuppressive Isopimarane Diterpenes From Cultures of the Endophytic Fungus Ilyonectria robusta - Ye, Ke; Lv, Xiao; Zhang, Xian; Wei, Pan-Pan; Li, Zheng-Hui; Ai, Hong-Lian; Zhao, Da-Ke; Liu, Ji-Kai (Frontiers in Pharmacology, 2022)
Five new isopimarane diterpenes, robustaditerpene A-E (1-5), which include19-nor-isopimarane skeleton and isopimarane skeleton, were isolated from the liquid fermentation of the endophytic fungus Ilyonectria robusta collected from Bletilla striata. The structure elucidation and relative configuration assignments of all compounds were accomplished by interpretation of NMR and HRESIMS spectrometric analyses and 13C NMR calculation. And the absolute configuration of 1-5 were identified by single-crystal X-ray diffraction and ECD calculation. All compounds were evaluated for immunosuppressive activity. Fortunately, compound 3 and 5 showed the immunosuppressive activity against the cell proliferation of and LPS-induced B lymphocytes with IC50 value at 17.4 μM and Con A-induced T lymphocytes with IC50 value at 75.3 μM, respectively.